Uso dos biomarcadores: molécula de lesão renal urinária-1, cistatina C, lipocalina associada à gelatinase neutrofílica e syndecan-1 para avaliação de possíveis alterações renais em recém nascidos com ou sem sepse - Barbosa, Joycilene da Silva (2021)
Renal changes are frequent and have a high mortality rate in the Neonatal Intensive Care Unit (nUTI). They can be triggered by sepsis or other infections, especially in premature infants, in which traditional markers, such as serum creatinine (sCr) and urinary output have limitations in the diagnosis. Thus, the study aimed to identify the urinary kidney injury molecule-1 (uKIM-1), cystatin and urinary cystatin (uCysC), lipocalin associated with serum and urinary neutrophilic gelatinase (sNGAL and uNGAL) and syndecan-1 in early diagnosis of kidney damage in premature newborn (NB) with neonatal infection, including sepsis. It is an observational and analytical study, with 62 newborn (24 with neonatal infection, 11 with sepsis and 27 from the control group) of nUTI, Medium Risk Units and Joint Accommodation of the General Hospital Dr. César Cals (HGCC), carried out between August 2019 and September 2020. Through serum and urine samples, biomarkers were measured by sandwich elisa and compared to the acute kidney injury (AKI) determination: Kidney Disease: Improving Global Outcome (KDIGO) neonatal, by urine output. No AKI was found in any of the participants through the neonatal KDIGO and the levels of the biomarkers were: uCysC ng / ml: 0.64 (0.2 - 2.29); sNGAL ng / ml: 0.85 (0.4 - 1.39); Syndecan-1 ng / ml: 17.53 (12.54 - 25.85); uKIM-1 ng / ml: 0.31 (0.17 - 0.83); uNGAL ng / ml: 3.14 (1.74 - 5.51); CysC (ng / mg-cr): 4.78 (1.9 - 25.63); NGAL (ng / mg-cr): 27.81 (14.29 - 58.98) and KIM-1 (ng / mg-cr): 3.32 (1.59 - 7.24). uCysC and uNGAL were significant for kidney damage in the sick group, indicating kidney damage, even before AKI was detected by the neonatal KDIGO. Among the demographic and clinical characteristics of the newborns was the presence of neonatal infection or sepsis (associated with uCysC [ng/mg-cr] and uNGAL [ng/mg-cr]), represented, respectively, by the values: 8.54 ( 2.97 - 30.07) in the neonatal infection group, 12.46 (2.09 - 47.1) in the sepsis group, with p=0.001; 35.05 (21.65 - 59.32) for neonatal infection, 54.69 (16.49 - 74.25) for sepsis, with p=0.009. Another finding in the study population was the length of hospital stay longer than 30 days (also associated with uCysC [ng/mg-cr] and uNGAL [ng/mg-cr]), in which in the receiver operator curve (ROC), the area under the curve (AUC) was, respectively: AUC=0.778; p=0.018; AUC=0.722; p=0.059; and when combined, AUC=0.783; p=0.016, demonstrating an important association with the prognosis of newborns in the sick group.